EVALUATION FOR NURSES IN KAP ANALYSIS FOR PALLIATIVE CARE PATIENTS WITH HEART FAILURE FACTOR - SATTAR , H; ZARIF , M; SHER , N (Biological and Clinical Sciences Research Journal, 2024)
Heart failure is a prevalent and debilitating condition, requiring effective palliative care to manage symptoms and improve quality of life in terminal stages. Nurses play a critical role in delivering this care, but their knowledge, attitudes, and practices can influence outcomes significantly. Objective: To evaluate the knowledge, attitudes, and practices of nurses working with palliative care patients with heart failure. Methods: A cross-sectional study was conducted in the Nursing Department of Nishtar Hospital, Multan from April 2023 to April 2024. A total of 100 nurses working in the ICU and Cardiology department with heart failure patients admitted for palliative care were included in the study. Data was collected through questionnaires. Knowledge was assessed by the 30-item Palliative Care Quiz for Nursing, attitude regarding death was evaluated by a 32-item Death Attitude Profile and practice was assessed by 6-item perceptions of preparedness and ability to care for the dying (PPACD) R-I scale. Results: The mean knowledge score was 13.8 ± 2.55 with a satisfactory score in only 46% of participants. Only 29% were aware of symptom management in terminally ill patients. The mean attitude score was 133.6 ± 108.4 and the mean practice score was 16.2 ± 5.1. No significant association between knowledge scores and previous palliative care training was noted (r=0.1) but attitude scores were positively related to age and experience. The approach acceptance (r=0.292) and neutral acceptance (r=0.339) were significantly associated with practice. Conclusion: Nurses working in the palliative care unit possessed unsatisfactory knowledge, attitudes, and practices to manage patients with heart failure. Intervention programs and the inclusion of palliative care subjects in the curriculum can improve these results and avert the healthcare hazard.